Instructional Leadership for Fostering Technology-Responsive Literacy Pedagogy: A Systematic Review of Principal Coaching in Text-Rich Elementary Classrooms - Savitri, Herlina; Supriyana, Heri (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
Instructional leadership has become increasingly important in strengthening literacy pedagogy within technology-responsive learning environments in elementary schools. However, existing studies have predominantly examined instructional leadership, literacy instruction, and classroom learning environments as separate constructs, leaving limited evidence regarding how principal coaching supports the development of integrated literacy pedagogy in text-rich classrooms. This study aims to synthesize empirical evidence on principal coaching practices that foster technology-responsive literacy pedagogy through instructional leadership in elementary education. A Systematic Literature Review (SLR) was conducted following the PRISMA framework. Literature was retrieved from the Scopus database using predefined inclusion and exclusion criteria, resulting in the selection of 16 peer-reviewed studies published between 2020 and 2025. The thematic synthesis identified four interconnected themes. First, instructional leadership is most effective when implemented through structured clinical coaching cycles that empower teachers and strengthen instructional decision-making. Second, principal coaching transforms text-rich classrooms into functional learning environments by integrating print-based and digital literacy resources that support technology-responsive pedagogy. Third, student participation increases through enhanced student agency, collaborative literacy practices, and meaningful interaction with multimodal learning resources. Finally, sustainable implementation depends on distributed leadership, data-informed instructional support, and adequate organizational resources. The review proposes an integrated conceptual framework demonstrating that principal coaching functions as a strategic mechanism linking instructional leadership with technology-responsive literacy pedagogy. These findings contribute to educational technology and instructional leadership literature by providing evidence-based recommendations for designing sustainable literacy ecosystems that combine pedagogical innovation, collaborative leadership, and technology-supported learning in elementary schools.